Exchanges of care and older adults in the context of the pandemic in Mexico - Estrada Iguíniz, Margarita; Warn Cruz, Lisa; Rojas García, Georgina (Revista de Antropología Social, 2022)
The article focuses on the study on family participation forms of Mexican elder group during the first months of COVID19 pandemic. In a context of family members who needed to reorganize their daily lives due to confinement and the reduction of economic activities, the elderly were, once again, a source of support and company. These group made available their financial and material resources to their close relatives, and their work, which was reflected in the care they provided to their loved ones. On the other hand, grown up sons and daughters sought a way to protect their parents. Through the exchange of resources and care, the members of the studied families achieved the organization of daily life required in the context of the pandemic and alleviate some of its most negative effects such as impoverishment and abandonment